Adaptive potential of winter common wheat varieties in the Penza region - S. V. Kosenko (Зерновое хозяйство России, 2024)
The current paper has presented the results of long-term study (2014–2023) of productivity, adaptability parameters and correlation between a genotype and environment of winter common wheat varieties in the forest-steppe conditions of the Penza region.   The purpose of the study was to determine the response of winter common wheat varieties in changing agroclimatic conditions according to productivity.   The vegetation conditions during the years of study varied in temperature and amount of precipitation, which served as a good background for conducting research on the issue in question. The objects for the study were 9 zoned varieties approved for cultivation in the Middle Volga region and 5 winter common wheat varieties developed by the FSBRI CBFC. The zoned winter common wheat variety ‘Fotiniya’ was used as a standard. The years of the varieties’ study were divided into favorable, typical (mean) and unfavorable (dry, excessively wet). Winter common wheat productivity in favorable years averaged 5.68 t/ha, in typical years it was 4.32 t/ha and 2.19 t/ in unfavorable years. As a result of determining the response of winter common wheat varieties in changing agroclimatic conditions according to productivity, there was proven a strong effect of environmental conditions and genotype. There have been proposed for breeding use such valuable and stable genotypes of winter common wheat as ‘Biryuza’, ‘Skipetr’, ‘Don-eko’, ‘Alyonushka’, ‘Pamyati Krivobocheka’, ‘Surskaya Nika’, ‘Dargo’, which should be placed on a high and medium agricultural background. The varieties ‘Fotiniya’ and ‘Klavdiya 2’ are highly adaptable to unfavorable cultivation conditions and will have an advantage over other varieties in medium and low agricultural backgrounds.